Ulama in Indonesia's Political Contestation: The Indonesian Ulama Council's Election Posts on Instagram - Anggraeni, Nur Najmi; Baktı, Ahmet Selman; Zainol, Siti Zulfa Palem Binti; Syahmirwan; Fathiyakan (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2024)
The article aims to explore the role of the Indonesian Ulama Council in the 2024 election contestation through election posts on Instagram. This study was conducted using the content analysis method. Data sources were obtained from the Indonesian Ulama Council's Instagram account. The data was obtained by observing posts from September 2023 to March 2024. The data obtained was then analyzed with three stages of qualitative analysis: data reduction, data display, and conclusion. Based on the data analysis, this study found that substantially, the election content posted by the Indonesian Ulama Council on Instagram is about peaceful elections and Muslim participation in elections. The study also found that the posting of election-related fatwas by the Indonesian Ulama Council on Instagram aims to raise awareness and encourage Muslims to exercise their voting rights in the election. Based on these findings, election-related posts by the Indonesian Ulama Council on Instagram represent the involvement of religious institutions in political contestation and the embodiment of ideological roles as a driving force for the successful implementation of elections in Indonesia.